X‐band low phase noise loop oscillator with differential outputs. Issue 13 (8th June 2015) - Yang, Ziqiang; Luo, Bangyu; Dong, Jun; Yang, Tao
Abstract : A novel X‐band low phase noise loop oscillator with differential outputs is proposed. A substrate‐integrated waveguide (SIW) resonator operated in TE120 mode is employed in the feedback loop of the oscillator as a frequency stabilisation element. Meanwhile, two other ports are connected to the same resonator for differential outputs, which can avoid the use of any additional active device or balun. Moreover, this oscillator can generate low‐phase noise signals owing to the high‐ Q SIW resonator. A prototype of the oscillator has been designed, fabricated and measured. Two anti‐phase output signals with good phase and amplitude accuracy are obtained at an oscillation frequency of 9.01 GHz. The measured phase noise is −104.3 dBc/Hz at 100 kHz offset, which corresponds to a figure of merit of −190.4 dB.